Peran public relation dalam membangun kepercayaan dan citra positif lembaga keuangan syariah di era transformasi digital - Aini, Mufidatul (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has transformed communication paradigms within financial institutions, including Islamic financial institutions that must adapt to modern consumer behavior. In this context, Public Relations (PR) plays an essential role in building public trust and strengthening a positive institutional image based on Islamic values. This study aims to analyze the role of PR in maintaining reputation and enhancing public trust in Islamic financial institutions during the digital era. This research applies a qualitative method with a library-based approach by reviewing nine scientific journals related to public communication, digital marketing, and Islamic banking. The findings reveal that digital-based PR enhances transparency, public education, and customer loyalty through technology-driven two-way communication. Collaboration between PR and digital marketing makes the dissemination of Islamic messages more effective and adaptive to digital society needs. Furthermore, Islamic ethical values such as sidq (truthfulness), amanah (trustworthiness), and tabligh (effective communication) serve as moral foundations that strengthen institutional integrity. These values make PR not merely a promotional tool but a medium of Islamic economic dissemination that contributes to the continuous strengthening of the positive image of Islamic financial institutions in a globalized era.